2021
DOI: 10.1021/acs.est.1c00417
|View full text |Cite
|
Sign up to set email alerts
|

Improving Predictions of Indoor Aerosol Concentrations of Outdoor Origin by Considering the Phase Change of Semivolatile Material Driven by Temperature and Mass-Loading Gradients

Abstract: Outdoor aerosols experience environmental changes as they are transported indoors, including outdoor-toindoor temperature and mass-loading gradients, which can reduce or enhance their indoor concentrations due to repartitioning driven by changes in thermodynamic equilibrium states. However, the complexity required to model repartitioning typically hinders its inclusion in studies predicting indoor exposure to ambient aerosols. To facilitate exposure predictions, this work used an explicit thermodynamic indoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 60 publications
(109 reference statements)
0
24
0
Order By: Relevance
“…Partitioning factor F i for residential settings as a function of indoor–outdoor temperature differences for (a) hydrocarbon‐like organic aerosol and (b) oxidized organic aerosol. Shaded area represents 95% confidence intervals, provided by Cummings and based on model results presented in Cummings et al 340 Red lines represent trends observed by Avery et al 341 …”
Section: How Temperature and Humidity Influence Indoor Chemistry Emis...mentioning
confidence: 99%
See 2 more Smart Citations
“…Partitioning factor F i for residential settings as a function of indoor–outdoor temperature differences for (a) hydrocarbon‐like organic aerosol and (b) oxidized organic aerosol. Shaded area represents 95% confidence intervals, provided by Cummings and based on model results presented in Cummings et al 340 Red lines represent trends observed by Avery et al 341 …”
Section: How Temperature and Humidity Influence Indoor Chemistry Emis...mentioning
confidence: 99%
“…Indoor sources of SVOCs contribute mass as well, especially if indoor air is cooler than outdoor air. Therefore, models that only consider mechanical removal (e.g., filtration and deposition) of particles can over‐ or underpredict the mass concentration of particles and their components 337–340 . As an example of this effect, Cummings et al 340 predicted the concentration of various chemical components in the aerosol phase for different indoor–outdoor temperatures and other factors for typical aerosols across 16 different US climate zones.…”
Section: How Temperature and Humidity Influence Indoor Chemistry Emis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor OA models have also employed these assumptions. [9][10][11][12][13][14] Recent laboratory and atmospheric measurements have challenged the validity of this assumption with evidence of OA that possess either a semisolid or a glassy, amorphous solid phase state. [15][16][17] Subsequent modeling work has since estimated that the annual-average phase state of atmospheric SOA is most oen semisolid in the troposphere over mid-latitude continental regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SO42 is only subject to physical losses indoors, while NO3 and NH4+ may additionally experience thermodynamic transformations. Temperature and relative humidity (RH) gradients between ambient and indoor conditions drive the partitioning behavior of semi‐volatile inorganic aerosol (IA) and OA constituents through volatilization or condensation, impacting indoor composition 3,18 . Furthermore, changes between outdoor and indoor RH affect the water content of aerosols via condensation and uptake by hygroscopic components, which further perturbs equilibria with gas phase compounds.…”
Section: Introductionmentioning
confidence: 99%